Adverse effects of dipyrone (Metamizole) use during pregnancy on offspring health: a systematic review and meta-analysis - Gabriel Moreira Lino; Felipe Shoji Ishibashi; George Alessandro Maranhão Conrado; Cristiane Campello Bresani-Salvi; Pauliana Valéria Machado Galvão (BMC Pregnancy and Childbirth)
Abstract Background This meta-analysis and systematic review aimed to review the health outcomes of offspring following dipyrone use during pregnancy. Methods A systematic literature search was conducted in MEDLINE, Embase, and the Cochrane Library to identify clinical trials or observational studies investigating women who used dipyrone during pregnancy (up to 16 August 2024). The data was analyzed using odds ratios (ORs) with inverse variance and Bayesian random effects models. Results Six case-control studies and four prospective cohort studies met the inclusion criteria. No association was found with birth defects (OR 1.27, 95% CI 0.83–1.77; I 2  = 39.94%; 3 cohorts and 1 case-control), major anomalies (OR 1.06, 95% CI 0.47–2.37; I 2  = 14.35%; 2 cohorts), infant leukemia (OR 1.25, 95% CI 0.86–2.22; I 2  = 72.82%; 2 case-controls), gestational loss (OR 0.80, 95% CI 0.57–1.13; 3 cohorts), prematurity (OR 0.99, 95% CI 0.80–1.21; I 2  = 0%; 3 cohorts), low birth weight, constriction of the ductus arteriosus, or renal and cardiac disorders. However, all analyses were of low or very low certainty. Conclusion No association was found between maternal use of dipyrone in the investigated outcomes, although these conclusions are limited by the quality of the included studies, sample size, and overall evidence. Further research with a better assessment of exposure is required to exclude risk.